2011
DOI: 10.1209/0295-5075/94/53003
|View full text |Cite
|
Sign up to set email alerts
|

Multihump soliton-like structures in interactions of lasers and Bose-Einstein condensates

Abstract: An investigation is made of multihump and periodic solutions of the semiclassical coupled equations describing laser radiation copropagating with a Bose-Einstein condensate. Solutions reminiscent of optical vector solitons have been found and have been used to gain understanding of the dynamics observed in the numerical simulations, in particular to shed light on the phenomenon of jet emission from a condensate interacting with a laser.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Such type of multipeaked stationary solutions exist in laser-BEC interactions and it has been shown that they can also explain the formation of bound state. Also, these triple-peak nonlinear wave can be associated with a series of asymmetric optical multipeak solitons on a continuous wave background [22].…”
Section: Case (I): X 1 + Ax 2 (Travelling Wave Solutions)mentioning
confidence: 99%
“…Such type of multipeaked stationary solutions exist in laser-BEC interactions and it has been shown that they can also explain the formation of bound state. Also, these triple-peak nonlinear wave can be associated with a series of asymmetric optical multipeak solitons on a continuous wave background [22].…”
Section: Case (I): X 1 + Ax 2 (Travelling Wave Solutions)mentioning
confidence: 99%
“…For nonintegrable multi-component nonlinear models formation of stable multihump solitary waves, a novel physical mechanism has been presented in [5]. These multi-hump optical solitons observed numerically in the models describing laser radiation copropagating with a Bose-Einstein condensate and used to shed light on the phenomenon of jet emission from a condensate interacting with a laser [6].…”
Section: Introductionmentioning
confidence: 99%